(untitled) (African Journal of Biomedical Research, 2021)
Tick infestation in dogs is a major concern to dog owners. The abundance and distribution of ticks and tick-borne diseases have been extensively reported, but not from the dog owner’s perspective. Herein, we examined tick infestation and density in dogs and the associated risk factors around Ibadan. Structured questionnaire was distributed among dog owners on knowledge of tick infestation. A total of 130 dogs of different breeds, ages and sex were examined in eight veterinary hospitals within Ibadan metropolis between July and September 2018 using purposive sampling. Risk factors include breeds, control methods, age, sex, geographical location and management. Common method of tick control employed by dog owners were; tick spray 18 (16.8%), tick powder 41 (38.3%), injections 22 (20.6%), and bathing 26 (24.3%). Dogs with the age less than 12 months were the most infested, while those within the age of 24 – 120 months were the least infested. Female dogs were more infested than the males. The prevalence of tick infestation in this study was 56.2% with the head region being the most predilection site of attachment of ticks. Rhipicephalus sanguineus was the most common tick infesting dogs. Demographic characteristic of dog owners, their knowledge on tick infestation, age of dogs, breed and sex have no significant influence on tick infestation. Previous tick infestation was highly significant (P = 0.001). Dogs domiciled in Ibadan were observed to be at risk of tick infestation. Continuous prophylactic and biosecurity measures could be strategically used in preventing tick infestation in this tropical region.